The Effectiveness of the SSCS (Search, Solve, Create, and Share) Learning Model for Increasing Mathematical Communication Skills and Numeracy Literacy - Putriana, Canthika; Haqiqi, Arghob Khofya (Universitas Islam Negeri Sunan Kudus, 2023)
The significance of mathematical communication skills and numeracy literacy is paramount for comprehending mathematical problems and concepts. Mathematical communication skills and numeracy literacy can be improved with innovative learning models that can create an active, creative, critical, and independent learning atmosphere, one of them is the SSCS model. The purpose of this study is to determine the effectiveness of the process of learning mathematics on the material of flat-sided geometric shapes using learning models to improve mathematical communication skills and numeracy literacy. This study adopted a quantitative approach within the framework of field research. The research population was all students of class VIII regular MTs Negeri 1 Kudus, totaling 250 students. Sampling was carried out by cluster random sampling technique and obtained as many as 61 students consisting of the experimental class and the control class. To collect research data, essay test, observations, and documentation were carried out. The results revealed a significant difference in the average value of mathematical communication skills, indicated by a significance value of 0.00 < 0.05. Additionally, the experimental class showed a medium interpretation increase of 52% in the normalized gain test, while the control class demonstrated a low interpretation increase of 22%. In numeracy literacy skills, there was also a difference in the average value, indicated by a significance value of 0.00 < 0.05. Additionally, there was an increase in the experimental class in the normalized gain test, with a medium interpretation improvement of 55%, whereas the control class showed a low interpretation increase of 25%. Based on the research data, the experimental class demonstrated a more significant improvement with the SSCS model compared to the control class. This led to the conclusion that applying the SSCS model effectively enhanced both mathematical communication skills and numeracy literacy. Pentingnya kemampuan komunikasi matematis dan literasi numerasi untuk pembelajaran matematika dalam memahami masalah dan konsep matematis. Kemampuan komunikasi matematis dan literasi numerasi dapat ditingkatkan dengan inovasi model pembelajaran yang dapat menciptakan suasana belajar aktif, kreatif, kritis, dan mandiri salah satunya menggunakan model SSCS. Tujuan penelitian ini yaitu untuk mengetahui efektivitas proses pembelajaran matematika pada materi bangun ruang sisi datar menggunakan model pembelajaran untuk meningkatkan kemampuan komunikasi matematis dan literasi numerasi. Jenis penelitian ini yaitu penelitian field research dengan pendekatakan kuantitatif. Populasi penelitian yaitu seluruh siswa kelas VIII regular MTs Negeri 1 Kudus yang berjumlah 250 siswa. Penarikan sampel dilakukan dengan teknik cluster random sampling diperoleh sebanyak 61 siswa yang terdiri dari kelas eksperimen dan kelas kontrol. Untuk mengumpulkan data penelitian dilakukan tes uraian, observasi, dan dokumentasi. Diperoleh hasil bahwa terdapat perbedaan rata-rata nilai kemampuan komunikasi matematis yang ditunjukkan nilai signifikansi 0,00 < 0,05 dan peningkatan kelas eksperimen pada uji gain ternormalisasi sebesar 52% interpretasi sedang dan kelas kontrol 22% interpretasi rendah. Pada kemampuan literasi numerasi juga terdapat perbedaan rata-rata nilai yang ditunjukkan nilai signifikansi 0,00 < 0,05 dan peningkatan kelas eksperimen pada uji gain ternormalisasi sebesar 55% interpretasi sedang dan kelas kontrol 25% interpretasi rendah. Berdasarkan data penelitian tersebut, karena pada kelas eksperimen menunjukkan peningkatan lebih baik dengan model SSCS daripada kelas kontrol. Disimpulkan bahwa penerapan model SSCS untuk meningkatkan kemampuan komunikasi matematis dan literasi numerasi menunjukkan hasil yang efektif.